Pushover Analysis of Harvard Dormitory Thursina International Islamic Boarding School Building with Inter Story Isolated System Modification - Rahman, Aulia; Fajarwati, Anisah Nur; Sholeh, Moch; Sugiarto, Agus (Jurnal Teknologi dan Manajemen, 2025)
Recently the demands of additional building functions have varied. These demands tend to affect structure stability because of the effects of additional mass. For example, Harvard Dormitory Thursina International Islamic Boarding School, located in Dau region, Malang city, East Java, Indonesia, a 11 x 8 m2 swimming pool is relocated on 4th floor. A big mass of pool certainly performs bigger lateral force due to seismic behaviour of structure itself. To reduce that, the IIS method is installed on the 3rd floor as it has damper effect along X and Y axis that is provided by LRB spring systems. IIS is widely used mainly in Japanese high-rise structures such as Shiodome Sumitomo building and Umeda Tower. To analyse the IIS modified structure, it is performed pushover analysis as controlled deformation is stated 18 in at rooftop. The results showed that 465 kN shear force and 160 mm story drift occurred on the 3rd floor which is the largest value compared to other stories. It is also obtained 230 mm lateral deflection of rooftop as the first plastic hinges are formed.